English additional language student teachers' development of oral strategic competence and confidence - Meyers, Rozanne Elanore (Rhodes University, Faculty of Education, Department of Education)
This case study sought to understand how oral strategic and discourse competence and confidence developed in student teachers using English, their additional language, firstly as a tool of learning and secondly, as a medium of instruction in education environments. Within the broad qualitative approach an interpretive framework was adopted using multiple data collection tools. This was in order to privilege detailed accounts of participants' experiences. Namely, unstructured interviews, drawings, observational checklists, and selfassessment questionnaires. Participants' oral strategic and discourse competence were assessed using an observation checklist as they presented micro-teaching lessons. Additionally, participants completed a self-assessment questionnaire, reflecting on their oral competence after conducting their micro-teaching lessons. These perceptions were confirmed through a discussion of drawings that illustrated how they perceived themselves during lectures when they had to use English during oral interaction with lecturers and fellow students. Finally, unstructured interviews were conducted after participants completed their micro-teaching lessons and after participants had completed their drawings. The raw data from the four tools were analysed using a thematic approach. Main themes and categories were analysed and discussed to provide answers to the research questions. Data correlated the attitude of participants towards English and their level of oral confidence and competence. The main findings were that students were motivated to develop their oral English competence because they believed it was an important skill for teachers to possess. This motivation also proved to be a leading factor in participants' competence despite the negative emotions they identified during spoken exchanges. Furthermore, the analysis found that collaborating with fellow students in making meaning of oral communication during lectures, increased students' oral competence and their confidence because they were communicating in smaller groups. However, in certain situations, collaborating with students also decreased their confidence. Findings indicated that reciprocal facial expressions and the body language of those who engaged orally with the student teachers, increased their oral confidence as it served as an indication to them that they were understood. Based on these findings, recommendations are made regarding interactions during lectures for teacher training programmes in Higher Education in South Africa, for lecturers and lecturing practices, and curriculum designers in the South African Department of Education.
Keywords: Student teaching -- South Africa; Communicative competence -- South Africa; Oral communication; Native language and education; Language arts; Verbal ability; Multilingual education